Entertaining race : performing Blackness in America - Dyson, Michael Eric (St. Martin's Press, 2021)
"For more than thirty years, Michael Eric Dyson has played a prominent role in the nation as a public intellectual, university professor, cultural critic, social activist and ordained Baptist minister. He has presented a rich and resourceful set of ideas about American history and culture. Now for the first time he brings together the various components of his multihued identity and eclectic pursuits. Entertaining Race is a testament to Dyson's consistent celebration of the outsized impact of African American culture and politics on this country. Black people were forced to entertain white people in slavery, have been forced to entertain the idea of race from the start, and must find entertaining ways to make race an object of national conversation. Dyson's career embodies these and other ways of performing Blackness, and in these pages, ranging from 1991 to the present, he entertains race with his pen, voice and body, and occasionally, alongside luminaries like Cornel West, David Blight, Ibram X. Kendi, Master P, MC Lyte, Ta-Nehisi Coates, Alicia Garza, John McWhorter, and Jordan Peterson. Most of this work will be new to readers, a fresh light for many of his long-time fans and an inspiring introduction for newcomers. Entertaining Race offers a compelling vision from the mind and heart of one of America's most important and enduring voices"--